(untitled) - Lynne Reid Banks (New York Avon Camelot, 1993)
"The Return of the Indian" by Lynne Reid Banks is the sequel to "The Indian in the Cupboard." In this enchanting children's fantasy, Omri, who once brought his toy Indian, Little Bear, to life, faces new challenges and adventures. When Little Bear faces danger in his own time, Omri and his friend Patrick return to the magical cupboard to help.
Keywords: Children's literature; Fantasy